STUDI EMPIRIS KEPUASAN KERJA, JOB INSECURITY, KOMITMEN ORGANISASI, DAN KEINGINAN BERPINDAH AKUNTAN PUBLIK DI SEMARANG - Mranani, Mudji (Jurnal Analisis Bisnis Ekonomi, 2008)
This research aim to check how far influence of Job Satisfaction, Jon Insecurity and organizational commitment to migratory desire of laboring accountant staff at Public Accountant Firm in Semarang Data Research obtained by judgement purposive sampling to laboring accountant staff at Public Accountant Firm residing in Semarang. Amount of responden which is competent to be used in this research counted 48 responden. Research data consist of information Job Satisfaction, Job insecurity and organizational commitment as free variable and migratory desire as variable tied. Analysis method the used is doubled linear regression model. Variable one until three tested by using t test o assess how far influence of is each free variable individually in explaining variable tied. While fourth variable tested by using test of f to assess ability of free variable to variable tied by together. Before hypothesis test beforehand to test classic assumtion. Result of classic assumption test indicate that do not there are multicolinierrity, heteroscedastisity, and auto correlation. Result of research indicate that Job Satisfaction, Job insequrity and organizational commitment have an effect on and negativity of significance to migratory desire. While job insecurity have on positive effect to migratory desire. Result of hypothesis test also indicate taht independent variable of job satisfaction, job insecurity and of organizational commitment by together have influence to migratory desire as variable of dependent.